To Surcharge or Not to Surcharge: An Empirical Investigation of ATM Pricing - Hannan, Timothy H.; Kiser, Elizabeth K.; Prager, Robin A.; McAndrews, James J. (The Review of Economics and Statistics, 2003)
This paper investigates depository institutions' decisions whether or not to impose surcharges (direct usage fees) on nondepositors who use their ATMs. In addition to documenting patterns of surcharging, we examine motives for surcharging, including both direct generation of fee revenue and the potential to attract deposit customers who wish to avoid incurring surcharges at an institution's ATMs. Consistent with expectations, we find that the probability of surcharging increases with both the institution's share of market ATMs and the time since surcharging was first allowed in the state, and decreases with increasing local ATM density. Further, we find evidence consistent with the use of surcharges to attract deposit customers who are new to the local banking market, but we find no evidence that larger banks use surcharges as a means to attract existing customers away from smaller local competitors.